2015
DOI: 10.1002/cssc.201500339
|View full text |Cite
|
Sign up to set email alerts
|

A Key concept in Magnesium Secondary Battery Electrolytes

Abstract: A critical roadblock toward practical Mg-based energy storage technologies is the lack of reversible electrolytes that are safe and electrochemically stable. Here, we report on high-performance electrolytes based on 1-ethyl-3-methylimidazolium chloride (EMImCl) doped with AlCl3 and highly amorphous δ-MgCl2 . The phase diagram of the electrolytes reveals the presence of four thermal transitions that strongly depend on salt content. High-level density functional theory (DFT)-based electronic structure calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 38 publications
4
43
0
1
Order By: Relevance
“…demonstrated the first fully inorganic and halide-free Mg electrolytes enabling reversible Mg plating and stripping78. In an effort to improve the safety, attempts have been made to replace the flammable organic solvents by ionic liquids91011.…”
mentioning
confidence: 99%
“…demonstrated the first fully inorganic and halide-free Mg electrolytes enabling reversible Mg plating and stripping78. In an effort to improve the safety, attempts have been made to replace the flammable organic solvents by ionic liquids91011.…”
mentioning
confidence: 99%
“…Although the first prototype Mg battery using stable Mo 6 S 8 as cathode was introduced over fifteen years ago, major challenges remain to be solved. [4][5][6][7][8] There is also intensiver esearch going on in the field of ionic liquid electrolytes, [9,10] which could offer safer Mg electrolytes regarding their flammability and volatility.N on-nucleophilic electrolytes with high oxidative stability open the possibility to employ organic materials in which weaki ntermolecularf orces enabler eversible electrochemical interactions and fast diffusion of Mg cations. Herein, we present an ew,g eneral, and robust approach towards achieving stable cycling of Mg batteries.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] There is also intensiver esearch going on in the field of ionic liquid electrolytes, [9,10] which could offer safer Mg electrolytes regarding their flammability and volatility.N on-nucleophilic electrolytes with high oxidative stability open the possibility to employ organic materials in which weaki ntermolecularf orces enabler eversible electrochemical interactions and fast diffusion of Mg cations. [4][5][6][7][8] There is also intensiver esearch going on in the field of ionic liquid electrolytes, [9,10] which could offer safer Mg electrolytes regarding their flammability and volatility.N on-nucleophilic electrolytes with high oxidative stability open the possibility to employ organic materials in which weaki ntermolecularf orces enabler eversible electrochemical interactions and fast diffusion of Mg cations.…”
mentioning
confidence: 99%
“…Recently, Bertasi et al reported Mg electrolytes based on 1-ethyl-3-methylimidazolium chloride (EMImCl) with AlCl 3 and amorphous δ-MgCl 2 exhibited highly reversible behavior. 37 2 , IL solvents BMIM-TFSI (l-n-butyl-3-methylimidazolium bis(trifluoromethyl sulfonyl)imide), PP 13 -TFSI (N-methyl-N-propylpiperidinium bis(trifluoromethyl sulfonyl)imide), and DEME-BF 4 (N,N-diethyl-N-methyl(2-methoxyethyl)-ammonium tetrafluoroborate), and DME and ACN (acetonitrile) organic cosolvents. 38 The failure owes to the strong coulombic attraction between the anions and the extremely charge-dense Mg 2+ cation, which prevents dissociation in solution to produce solvated mobile Mg 2+ and the strong association could not 27 In view of few reports about the compatibility of ILs-based magnesium electrolytes with cathodes, an appropriate electrolyte formulation for Mg batteries and hybrid Mg-Li batteries was further identified for practical application.…”
mentioning
confidence: 99%